Assistance for Early Detection of High-Risk Pregnancy - Endang Wahyuningsih (WASATHON Jurnal Pengabdian Masyarakat, 2026)
Pregnancy is a physiological process that women will experience during their reproductive years. In Indonesia, maternal mortality is a major issue in the health sector. One of the key indicators of a country's health status is the Maternal Mortality Ratio (MMR). The MMR is an important indicator that describes the number of women who die from causes related to pregnancy complications or their management during pregnancy, childbirth, and the postpartum period. The target of the Sustainable Development Goals (SDGs) by 2030 is to reduce the MMR to below 70 per 100,000 live births. The phenomenon of high-risk cases in 2023 is assessed based on potential emergencies, warning signs, urgent situations, total case numbers, and total referrals. The number of potential emergencies is 11 cases. The number of warning sign cases is 19, while there are 192 urgent cases. Over one year, the total number of cases is 29, with 15 referrals to hospitals and 14 cases handled at primary health centers. Efforts to reduce maternal mortality include an integrated antenatal care program. Integrated antenatal care is a comprehensive and coordinated service at health facilities that includes promotive, preventive, curative, and rehabilitative efforts. The number of pregnant women participating in the service activities is 14 Therefore, the proposed community service is related to the high-risk pregnant women early detection assistance program. The results of the service activities show that the majority of pregnant women (71.4%) are aged 20-29 years, but education about high-risk pregnancy is still necessary, especially for the age group of 30-39 years (28.6%) who are more vulnerable. The high level of education (50% high school, 42.9% associate/bachelor’s degree) supports health understanding, but access to health information remains limited for housewives. This assistance is very important to increase awareness and prevent complications, especially for pregnant women aged 30-39 years who require special attention